HEGEMONI LELUHUR SUKU DAYAK BANUAQ DALAM NOVELUPACARA KARYA KORRIE LAYUN RAMPAN - Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA, 2025)
The novel Buruh by Korrie Layun Rampan is a novel published by PT Gramedia Widiasarana Indonesia in 1978. This novel was written based on a culture that is very thick with the customs and beliefs of the Banuaq Dayak tribe, and is packed with magical and spiritual surprises. This is reflected in spiritual activities and beliefs that are still animistic and dynamic in the level of belief in ancestral power. There are important things that should be questioned, what is the form of ancestral hegemony of the Banuaq Dayak tribe, and how to resist the hegemony of the Banuaq Dayak tribe ancestors. To solve this problem, the author uses a sociological literary approach that focuses on Gramsci's Hegemony theory.